The Role of Concentration on Football Playing Skills Cintasi FC (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of the study was to determine the role of concentration on football playing skills Cintasi Fc. The type of research used is descriptive research of a correlational nature. The population in this study was all Cintasi Fc players. The sample was 20 Cintasi Fc players.The sampling technique used is purposive sampling, which is a sampling technique with the researchers' own considerations so that it can represent a population of 20 people. The collected ATA is analyzed statistically, descriptively and infrencially for the purposes of testing research hypotheses. The accumulated football playing skill test instruments (dribble test, passing test, shooting test) are then used as T-scores.The concentration test uses a questionnaire with the Likert Scale. The result of the study was that football playing skills had a significant relationship with concentration with a significant value of 0.000>0.05. So it was decided Ha was accepted which means there is a significant relationship between variables. The conclusion of this study is that the psychological aspect of concentration greatly determines the success of players in playing football.